PENEGAKAN HUKUM BERDASARKAN PERATURAN MAHKAMAH AGUNG NOMOR 2 TAHUN 2012 TENTANG PENYESUAIAN BATASAN TINDAK PIDANA RINGAN DAN JUMLAH DENDA DALAM KITAB UNDANG-UNDANG HUKUM PIDANA DIKAITKAN DENGAN PUTUSAN PENGADILAN NEGERI INDRAMAYU NOMOR: 79/PID.C/2013/P - Hidayat, Taufik; Arifin, Jajang (Universitas Wiralodra, 2017)
Theft as arranged in Article 362 of the Criminal Code, it is a basic principle of theft of crime in general, so that Law Enforcement Apparatus such as Police, Prosecutor and Judge in handling theft cases refer to that Article. Whereas in addition to the article there is also article 364 of the Criminal Code which regulates specifically about theft limits of not more than Rp. 2.50, - (two hundred and fifty rupiah) is a light theft. The Supreme Court on February 27, 2012 has issued the Supreme Court Regulation Number 2 of 2012 on Adjustment of Limitations of Light Criminal Act and Penalties in the Criminal Code to be referred to the Law Enforcement Apparatus in Handling Light Theft. The study aims to examine the detention procedure conducted by the investigator and the prosecutor against the defendant in the criminal case register No. 79 / Pid.C / 2013 / PN.Im pursuant to the Supreme Court Regulation Number 2 of 2012 on Adjustment of Mild Crimes and Amount of Penalties in the Criminal Code, and to know the legal considerations of the Panel of Judges in the judgment of the defendant in a criminal case register Number: 79 / Pid.C / 2013 / PN.Im.